Socio-Demographic Profile as Determinants of Perceived Effectiveness of Corporate Social Responsibility: The Case of a Private Telecommunication Company in the Kingdom of Bahrain - Enriquez, Jonas (Technium Social Sciences Journal, 2020)
This research sought to ascertain the effectiveness of company’s CSR based on the perception of the workers in terms of age, gender and working position in relation to accountability, sustainability and transparency. The study used descriptive method with self-made questionnaire within the context of the principles of corporate social responsibility. Purposive and random samplings were used with 25% of the sample respondents considered in the total population. Multivariate Analysis was applied in the dependent and independent variables. Based on the results, the activities of corporate social responsibility in terms of accountability, sustainability and transparency were effectively practiced by the company. But as to demographic profile of the respondents, only age found significant to corporate social responsibility. And the significance was attributed only to transparency. As perceived by the respondents, among the three groups in the age profile, only group 3 which 27-30 of age was statistically significant to transparency. As such the null hypothesis was qualified to reject in 0.10 in the age level of 27-30. Management with good contact with the employees remained honest. Transparency of the business developed trust and attributed to make employees felt that they were working for organization with quality standards. Matured employees preferred the management to be transparent. More matured employees, the more awareness they perceived to the practices of the CSR by company. When management was transparent, matured employees were effective. Notwithstanding, the other demographic profiles such as gender and working position of the employees were not statistically significant.